PENGARUH KOMITMEN, KOMPETENSI DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI UNIVERSITAS ALKHAIRAAT PALU - Abadiyah, Ani Khuryatul (Katalogis, 2014)
This research aimed to analyze the effect of Commitment, Competence, and work experience on employee’s performance simultaneously and partially. Respondents on the study were 68 Alkhairaat University employees and the sampling method used was census technique.A multiple regression analysis was employed for this research. Study result shows that commitment, competence, and work experience simultaneously and partially have positive and significant impact on employee’s performance of Alkhairaat University Palu. The determination coefficient as indicated by R-square has a value of 0.563 which shows that 56,3% variability of employee’s performance is affected by commitment, competence, and work experience,while the rest as much as 43,7% is explained by other variables that are not studied in this research.